Identifying Gaps in Post-Exposure Rabies Prophylaxis in Hunan Province, China - Keith, Marie (My University, 2018)
My MPH Field Experience was completed in summer 2016 at the China CDC in Beijing. China experiences the second highest burden globally of human rabies deaths annually. Almost all of these deaths are due to canine rabies and transmitted from the dog population of China, in which rabies is endemic. Eliminating the disease from the dog population is the most significant way to reduce the incidence of the disease in humans. However, in the meantime, post-exposure prophylaxis (PEP) administered to the appropriate patients is necessary to reduce the number of fatalities due to the disease. During my field experience at the China CDC, I participated in a study to investigate the capabilities of clinics to administer rabies PEP successfully in Hunan Province, China. The study additionally followed potentially exposed patients at several clinic sites to identify gaps in post-exposure prophylaxis administration. This study found that wound washing, the first essential step in rabies PEP, is often neglected or inadequate; additionally, trained healthcare workers struggle to appropriately categorize patients according to their level of risk and therefore patients do not receive adequate PEP; furthermore, even patients whose risk levels are appropriately determined do not consistently receive the correct PEP either due to a lack of understanding among healthcare workers or due to lack of access to the necessary biologics. These gaps identified highlight some important target areas for improvement in the area of PEP delivery.
Keywords: rabies; China; post-exposure prophylaxis